Kansas Fertilizer Research 2013 - Dorivar Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2014)
The 2013 edition of the Kansas Fertilizer Research Report of Progress is a compilation of data collected by researchers across Kansas. Information was contributed by faculty and staff from the Department of Agronomy, Kansas agronomy experiment fields, and Agricultural Research Southeast Agricultural Research Center and research-extension centers. We greatly appreciate the cooperation of many K-State Research and Extension agents, farmers, fertilizer dealers, fertilizer equipment manufacturers, agricultural chemical manufacturers, and representatives of various firms who contributed time, effort, land, machinery, materials, and laboratory analyses. Without their support, much of the research in this report would not have been possible. Among companies and agencies providing materials, equipment, laboratory analyses, and financial support were Agrium, Inc.; Cargill, Inc.; Deere and Company; U.S. Environmental Protection Agency; FMC Corporation; Fluid Fertilizer Foundation; Foundation for Agronomic Research; Honeywell, Inc.; Hydro Agri North America, Inc.; IMC-Global Co.; IMC Kalium, Inc.; Kansas Agricultural Experiment Station; Kansas Conservation Commission; Kansas Corn Commission; Kansas Department of Health and Environment; Kansas Fertilizer Research Fund; Kansas Grain Sorghum Commission; Kansas Soybean Commission; Kansas Wheat Commission; Iogen Corporation; MK Minerals, Inc.; Nutra-flo; Monsanto; Pioneer Hi-Bred International; International Plant Nutrition Institute; Pursell Technology, Inc.; Servi-Tech, Inc; The Sulphur Institute; Winfield Solutions; and U.S. Department of Agriculture-Agricultural Research Southeast Agricultural Research Center Service. Special recognition and thanks are extended to Troy Lynn Eckart of Extension Agronomy for help with preparation of the manuscript; Kathy Lowe and Melissa Pierce, the lab technicians and students of the Soil Testing Lab, for their help with soil and plant analyses; and Mary Knapp of the Weather Data Library for preparation of precipitation data. Contributors A.R. Asebedo, Graduate Student, Dept. of Agronomy, K-State, Manhattan L.M. Bastos, Graduate Student, Dept. of Agronomy, K-State, Manhattan H.D. Bond, Assistant Scientist, Southwest Research-Extension Center, Tribune C.L. Edwards, Graduate Student, Dept. of Agronomy, K-State, Manhattan R. Florence, Research Assistant, Dept. of Agronomy, K-State, Manhattan T.J. Foster, Graduate Student, Dept. of Agronomy, K-State, Manhattan G. Hettiarachchi, Associate Professor, Soil and Environmental Chemistry, Dept. of Agronomy, K-State, Manhattan D.B. Mengel, Professor, Soil Fertility and Nutrient Management, Dept. of Agronomy, K-State, Manhattan C.W. Rice, Professor, Soil Microbiology, Dept. of Agronomy, K-State, Manhattan D.A. Ruiz Diaz, Assistant Professor, Soil Fertility and Nutrient Management, Dept. of Agronomy, K-State, Manhattan A.J. Schlegel, Agronomist, Southwest Research-Extension Center, Tribune D.W. Sweeney, Soil and Water Management Agronomist, Southeast Agricultural Research Southeast Agricultural Research Center Center, Parsons
Keywords: Kansas Agricultural Experiment Station contribution; no. 14-304-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1103; Kansas; Agronomy; Fertilizer; Yield; Application; Nutrients